Juridical Analysis of the Destruction of Modified Exhaust Pipes by Palangka Raya Police from the Perspective of Human Rights Protection - Syafuan Nor, Muhammad; Setiono, Joko; Hamid, Supardi (Greenation Publisher & Yayasan Global Resarch National, 2025)
The phenomenon of using modified (loud) exhaust pipes, known as knalpot brong, in various regions of Indonesia, including Palangka Raya City, has caused public unrest due to noise pollution disrupting comfort and public order. In response, the Palangka Raya Police Department conducted enforcement and destroyed 510 modified exhaust pipes as part of law enforcement efforts. This study aims to analyze the legality of these actions from the perspective of positive law and review them within the framework of human rights protection. The research method used is normative juridical with a legislative approach and case study. Based on Article 285 paragraph (1) of Law No. 22 of 2009 and Minister of Environment and Forestry Regulation No. 56 of 2019, these actions have a strong legal basis. However, from the human rights perspective as regulated in Articles 28A to 28J of the 1945 Constitution and Law No. 39 of 1999 on Human Rights, the destruction of personal property such as exhaust pipes must still consider principles of proportionality, justice, and a humane approach. Law enforcement that ignores these aspects may potentially violate personal property rights. The study results indicate that the destruction of knalpot brong by authorities can be legally and ethically justified as long as it is carried out with correct procedures and prioritizes respect for citizens' fundamental rights. There is a need for more intensive socialization and legal education to raise public awareness and foster a culture of civilized traffic order.